THE DEVELOPMENT OF MILITARY ART IN THE PERIOD OF AMIR TIMUR (American Journal of Pedagogical and Educational Research, 2023)
During his 35-year rule, the master Amir Temur was ready to fight against the powerful rulers of his time for the peace and tranquility of his country. In this article, we will consider the structure and essence of the military art used by Amur Temur in the battles.